2018
DOI: 10.1002/bse.2189
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the failure factors of eco‐friendly home appliances based on a user‐centered approach

Abstract: Pro‐environmental consumption is necessary for sustainable development, but the sales of eco‐friendly products have been limited. In this regard, the present study analyses the failure factors of eco‐friendly product consumption activation from the consumer's perspective, specifically focusing on detergent‐free washing machines, which are representative innovative products of eco‐friendly home appliances. This study analyses: (1) the attitude‐behaviour gap that occurs in the consumer decision‐making process, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Such phenomenon points out the attitude–behavior gap which has long been discussed in previous literature (Gifford & Sussman, 2012; Lutz, 1991; Stern, 2000), including in the domain of pro‐environmental behavior (Aschemann‐Witzel & Niebuhr Aagaard, 2014; Carrus et al, 2008; Chintakayala et al, 2018; Shin et al, 2018), which is simply called the “environmental attitude–behavior gap,” “environmental gap” (Redondo & Puelles, 2017), or “ethical purchasing gap” (Nicholls & Lee, 2006). The fact that attitudes do not always correlate to a subsequent change in behavior can be attributed to a moderator effect (Alwitt & Berger, 1993; Gifford & Nilsson, 2014; Papaoikonomou et al, 2011; Stojanova et al, 2021).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Such phenomenon points out the attitude–behavior gap which has long been discussed in previous literature (Gifford & Sussman, 2012; Lutz, 1991; Stern, 2000), including in the domain of pro‐environmental behavior (Aschemann‐Witzel & Niebuhr Aagaard, 2014; Carrus et al, 2008; Chintakayala et al, 2018; Shin et al, 2018), which is simply called the “environmental attitude–behavior gap,” “environmental gap” (Redondo & Puelles, 2017), or “ethical purchasing gap” (Nicholls & Lee, 2006). The fact that attitudes do not always correlate to a subsequent change in behavior can be attributed to a moderator effect (Alwitt & Berger, 1993; Gifford & Nilsson, 2014; Papaoikonomou et al, 2011; Stojanova et al, 2021).…”
Section: Introductionmentioning
confidence: 66%
“…Green purchase behavior is evolving and is of growing interest to academic and business circles (Cherian & Jacob, 2012; Dangelico et al, 2017). To encourage the adoption of green products which can further link to sustainable consumption (Brown & Kasser, 2005; Park & Lin, 2018; Shin et al, 2018), it is important to identify moderators that can enhance the consistency between attitude and behavior in the consumption of green products. A clear understanding of the interplay between attitude and moderators on the actual green products behavior is useful for green products business and practitioners in their endeavors to develop business and marketing strategies to align with their targeted consumers and to facilitate the consumption of green products which, in turn, encourages the growth of green products and paving ways for sustainable consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Environmentally fashion can be described as a fashion involving with an overall process that can maximise the benefits to all wherein minimise the carbon footprint impacts (Joergens, 2006). Based on this systematic review, two studies were focussing on clothing (Khare & Varshneya, 2017;Matthews & Rothenberg, 2017); four studies of general product (Kim et al, 2016;Paparoidamis & Tran, 2019;Saleem et al, 2018;Shin et al, 2018); three studies of luxury items (Ali et al, 2019;Fiore et al, 2017;Han et al, 2019), while nine studies were focussing on cosmetics (Ahmad & Omar, 2018;Amos et al, 2019;Baden & Prasad, 2016;Chin et al, 2018;Ghazali et al, 2017;Hsu et al, 2017;Kahraman & Kazançoğlu, 2019;Ndichu & Upadhyaya, 2019;Pudaruth et al, 2015;). Past research by Khare and Varshneya (2017) show that relatives and friends are not important drivers in influencing the organic clothing purchase decisions of youths in India.…”
Section: Eco-fashionmentioning
confidence: 99%
“…However, another research initiative by Shin et al (2018) showed a negative relationship of ecoconsciousness among customers in dealing to purchase the detergent-free washing machines. Moving to green luxury products, several previous studies showed that consumers are started to put their attention on the concept of environmentally friendly and sustainable luxury involving wine, automobile and airplane services (Ali et al, 2019;Fiore et al, 2017;Han et al, 2019).…”
Section: Eco-fashionmentioning
confidence: 99%
“…Therefore, the focus could be understood as more environmental than social or economic, in which case, these two conceptions of green consumption lack coherence. However, the meaning of PECB, has been shifting towards that of SCB in recent years as can be seen in the work by [32,[122][123][124][125]. If this was to be taken into account in the comparison of I1 and I2, then the overlap between "green" and "sustainable" becomes even more clear.…”
mentioning
confidence: 99%